Online dictionary skills - Lew, Robert (Trojina, Institute for Applied Slovene Studies/Eesti Keele Instituut, 2013)
Successful dictionary use requires two ingredients: (1) high-quality, user-friendly dictionaries and (2) dictionary users who know what they are doing. The bulk of current research effort within lexicography concentrates on making better dictionaries, with new opportunities afforded by the electronic medium. In contrast, the other ingredient — educating the user — receives comparatively little attention. The present contribution looks at dictionary reference skills in an effort to determine how traditional print dictionary skills need to evolve in order to allow users to get the most out of electronic dictionaries, in particular those offered online. The most comprehensive overview of dictionary skills to date has been Nesi (1999). Nesi’s list is here systematically reviewed, considering the relevance of each item in the context of online dictionaries. Novel ways of accessing lexicographic data are the most prominent quality of electronic dictionaries. The skills involved are sought by examining a selection of relevant literature on search techniques in electronic dictionaries, as well as some work done in the area of web search skills.
Keywords: electronic dictionary; online dictionary; dictionary skills; reference skills; internet skills; digital literacy; information literacy